AB0904 EFFECTIVENESS AND SAFETY OF RITUXIMAB IN SYSTEMIC AUTOIMMUNE DISEASES: A CASE SERIES DESCRIBING THE EXPERIENCE OF AN AUTOIMMUNE DISEASES UNIT IN A 3-YEAR PERIOD. (June 2019) - Suárez, Milagros; Argibay, Ana; Portela, Clara; Lima, Olalla; Rodríguez Ferreira, Lorena María; Estevez, Melania; Maure, Brenda; Triñanes, Caritina Vázquez; Gimena, Beatriz; Lorenzo, Rut; Fernandez, Julian; Rivera, Alberto; et al.
Abstract : Background: Rituximab (RTX) is a drug composed of chimeric monoclonal antibodies against the CD20 protein, producing a depletion of B lymphocytes. Nowadays, it is used to treat severe and refractory systemic autoimmune diseases (SAD). Objectives: Analysing the effectiveness and safety of RTX in patients with SAD in clinical practice. Methods: We conducted a retrospective analysis of patients with SAD treated at least once with RTX in the autoimmune diseases unit of our hospital in the last 3 years. We evaluated demographic, clinical and serological variables as well as the presence of adverse events (AE). Results: Twenty two patients have been included (13 women and 9 men, mean age 63 ±15 years). The diagnosis were ANCA-associated vasculitis (31, 8%), cryoglobulinemic vasculitis (18, 2%), autoimmune hemolytic anemia (13, 6%), systemic lupus erythematosus (9, 1%), immune thrombocytopenia in antiphospholipid syndrome (9, 1%) and one each of: Felty syndrome, IgG4-related disease, necrotizing myopathy and systemic sclerosis. Indications for treatment were renal disease in 36, 4% of the cases, haematological manifestations in 27, 3%, skin involvement in 13, 6%, neurologic manifestations in 9, 1% and other different reasons in the remaining 13, 6%. RTX was used after therapeutic failure with previous treatments in 81.8% and as first line treatment in only 18.1% of the cases. RTX dose was 375 mg/m2 once weekly for 4 doses (54, 5%) and 1000 mg on days 1 and 15 (45, 5%). After rituximab, 77, 3% of patients had complete response, 9, 1% partial response, and 13, 7% non-responding. There were 14 AE reported in 10 of the 22 patients (45, 5%) (See table). Three severe infections were found: were 2 patients with invasive pulmonary aspergillosis and 1 patient with invasive cryptococcosis. All of them died within the next month after beginning RTX. One of those who were diagnosed of arpegillosis had never received steroids. The other two were treated with high dose of steroids for several months. One patient had a nonischemic cardiomyopathy (NIC) with systolic dysfunction that resolved 4 months after RTX discontinuation. Conclusion: As far as we are concern, RTX is a useful and pretty safe biological agent in the treatment of refractory SAD. However, we must be aware of rare adverse effects such as NIC. In addition, given the potential severity of the infections found (although not totally attributable to RTX), we must closely follow up these patients for early diagnosis, treatment and even starting profilaxis in high risk patients. References: [1] Cheungpasitporn W, Kopecky SL, Specks US, Bharucha K. Non-ischemic cardiomyopathy after rituximab treatment for membranous nephropathy. J Renal Inj Prev. 2017;6(1):18-25. Doi: 10.15171/jrip.2017.04 [2] Fianchi L, Rossi E, Murri R, De Stefano V, Pagano L.. Severe infectious complications in a patient treated with Rituximab for idiopathic thrombocytopenic purpura. Ann Hematol. 2007 86;225-226. DOI: 10.10.1007/s00277-006 Disclosure of Interests: None declared